2020
DOI: 10.3390/ijms21031068
|View full text |Cite
|
Sign up to set email alerts
|

StABI5 Involved in the Regulation of Chloroplast Development and Photosynthesis in Potato

Abstract: Abscisic acid (ABA) insensitive 5 (ABI5)—a core transcription factor of the ABA signaling pathway—is a basic leucine zipper transcription factor that plays a key role in the regulation of seed germination and early seedling growth. ABI5 interacts with other phytohormone signals to regulate plant growth and development, and stress responses in Arabidopsis, but little is known about the functions of ABI5 in potatoes. Here, we find that StABI5 is involved in the regulation of chloroplast development and photosynt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…In potato, StABI5 plays an important role in the regulation of tuber dormancy through the controlling of the auxin signaling pathway. In addition, StABI5 regulates the genes (i.e., SUAR and AUX) downstream of the auxin signaling [ 24 ].…”
Section: Main Textmentioning
confidence: 99%
“…In potato, StABI5 plays an important role in the regulation of tuber dormancy through the controlling of the auxin signaling pathway. In addition, StABI5 regulates the genes (i.e., SUAR and AUX) downstream of the auxin signaling [ 24 ].…”
Section: Main Textmentioning
confidence: 99%
“…Phytohormone ABA plays key roles in vegetative, seed dormant and germination, and biotic and abiotic stresses such as drought, salt stress, and pathogen infection ( Jurriaan et al, 2009 ; Zhao et al, 2016 ; Vishwakarma et al, 2017 ; Kumar et al, 2019 ). ABI5 is a key transcription factor in regulating the expression of ABA-responsive genes in the ABA signaling pathway ( Skubacz et al, 2016 ; Zhu et al, 2020 ). Previous study revealed that ABI5 was phosphorylated at Thr-35, Ser-36, Ser-41, Ser-42, Ser-138, Ser-139, Ser-145, and Thr-201 residues in Arabidopsis ( Hu and Yu, 2014 ; Yu et al, 2015 ), of which Ser-42, Ser-145, and Thr-201 sites of ABI5 were phosphorylated by SnRK2s protein kinases ( Fujii and Zhu, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Potato is an important food crop in the world, occupying the fourth rank after wheat, rice, and corn (Zhu et al 2020). However, because of its high sensitivity, biotic and abiotic constraints limit the productivity of this plant (Chacón-Cerdas et al 2020).…”
Section: Discussionmentioning
confidence: 99%